Pre-Marital Screening: Thalassemia Trait and Iron Deficiency Anemia in Rahim Yar Khan, Pakistan - Muhammad Bilal Ghafoor, Sana Khan, Faiza Sarwar, Muhammad Saleem Leghari, Saleha Babar, Qazi Mohammad Irfan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: β- thalassemia Minor (BTM) and Iron Deficiency Anemia (IDA) are the main causes of microcytic hypochromic anemias currently in Asian subcontinent. Healthcare facilities in Pakistan have to encounter massive number of patients with anemias every day, where we need to distinguish between (IDA) and (BTM). A number of discrimination indices have been suggested for rapid differentiation of these entities over parameters achieved from automated blood-count analyzers. Objective. To determine the prevalence of β-thalassemia and IDA amongst the unmarried youngsters of Rahim Yar Khan. Methods: A cross-sectional study performed in Sheikh Zayed Medical College/Hospital Rahim Yar Khan, Pakistan in 04 months from October 2021 to February 2022, 506 unmarried youngsters were included in the study. CBC, Serum Ferritin and Hb Electrophoresis were performed in Hematology Section, Pathology Department of SZMC Rahim Yar Khan. Results: Out of 506 subjects, the prevalence of beta thalassemia trait was found 3.3% in males followed by 2.2% in females whereas the prevalence of IDA was 1.7% in males followed by 1.3% in females. Conclusion: These results indicates that intensive education and awareness strategies are necessary to increase consumption of iron-rich dietary sources. This screening program is beneficial in prevention of high-risk marriages. Screening of spouses by pre-marital screening program is an actual way to control β-thalassemia major.